IbM Kampung Tempe Tenggilis Kauman Surabaya - erma yuliaty; Siti Mundari; Zainal Arief (JPM17: Jurnal Pengabdian Masyarakat, 2017)
Tenggilis Kauman is an area in eastern Surabaya, since long time until now many of its citizens produce tempe so that the area is known as Kampung Tempe. Among the many tempe craftsmen there are Mr. Nurhasan and Mr. Poniman. Mr. Nurhasan started producing tempe since 1970. Currently the production amount has reached 2.5 quintals. While Mr. Poniman in 1970 is still a hawker tempe production of Mr. Nurhasan but then produce their own and current production level of about 40 kg per day. Their production has been taken by market traders as well as some made tempeh chips.               Although the demand for their tempe is now relatively many but in the production process both (Mr Nurhasan / Partners I) and (Mr. Poniman / Partners II) are often constrained peeler tempe equipment that is sometimes fussy that production is forced to pause. This is because the soybean skin peeler is outdated / old which since the first production until now has never been replaced. To maintain its continuity, the tool is engineered to keep it in production as expected.               Over time to increase their income they also produce chips that dititipkan in stores and fulfill orders. Yet tempe chips they produce often get complaints from consumers because of their plastic adhesive tool is not enough power so that plastic packaging can be open chips that cause kripik sluggish.               Problems that disrupt the production process above shows that both Part I and Partners II have not understood about business management so do not understand the need to change the production equipment, the need to calculate the cost of production and the need for bookkeeping of operating income loss so that businesses run so far not running optimally . Keywords: tempe village, soybean peeler, plastic adhesive, business management